SINERGI ORANG TUA DAN SEKOLAH:MEMBANGUN KEMITRAAN UNTUK OPTIMALISASI PERKEMBANGAN ANAK USIA DINI - Hamid Patilima; Awlya Nanda Awhar; Septina Suryati; Berka Nasridawati Situmorang; Betty Irawati Simatupang (JOURNAL OF COMMUNITY DEDICATION, 2025)
This research examines the effectiveness of a community service program in building partnerships between parents and schools to optimize early childhood development in Batam City. The lack of parental involvement in early childhood education, especially in urban areas with high levels of parental busyness, forms the background of this study. The implementation method used a participatory and collaborative approach with quantitative data from pre-test and post-test and qualitative data from interviews, observations, and focus group discussions. The program was implemented in five stages: needs analysis, socialization, training and capacity building, implementation assistance, and evaluation and reflection, involving 60 participants from TK Visi Kudus Indonesia and the educational community in Batam City. The results showed an increase in understanding of the partnership concept by 37.5%, an increase in partnership activities by 36.3%, and a positive impact on child development with an average improvement of 28% in aspects of independence, self-confidence, communication skills, learning motivation, and social skills. The multi-platform communication approach successfully increased parental participation to 84.8% by the end of the program. This research contributes to developing a contextual partnership model that combines conventional and digital approaches to accommodate the characteristics of urban families. Recommendations proposed include integrating the program into school policies, diversifying communication strategies, developing family curriculum, establishing support networks among parents, and expanding partnership coverage with the wider community to ensure sustainability of synergy between parents and schools in optimizing early childhood development.